Improvement of electrolyte flow field during through-mask electrochemical machining by changing mask wall angle. (January 2017) - Wang, Guoqian; Li, Hansong; Qu, Ningsong; Zhu, Di
Abstract: Hole arrays are a common mechanical structure in engineering components. Through-mask electrochemical machining has shown good feasibility in the field of machining difficult-to-cut metal parts with a hole array. The electrolyte flow field is an important factor to affect the process of electrochemical machining, therefore, the improvement of electrolyte flow field is always the key point of electrochemical machining. In this paper, a mask with cone-shaped holes is used to improve the electrolyte flow of through-mask electrochemical machining. The effects of mask wall angle on electrolyte flow are researched by using computational fluid dynamics. Four mask wall angles at 90°, 120°, 140° and 160° are analyzed numerically. The simulated results show that a mask with cone-shaped holes is beneficial to electrolyte flow during through-mask electrochemical machining, especially when the mask wall angle is more than 140°. In order to verify the simulated results, four angles of mask wall are applied to machining experiment. The experimental results indicate that the most reasonable mask wall angle is 140°. At this mask wall angle, the average diameter of fabricated holes is 2.764 mm, and the deviation of diameter is less than 0.1 mm. Meanwhile, the taper angle of fabricated holes is less than 5.8° and the deviation in roundness is 12.04 μm.